A feast for crows - Martin, George R.R. 1948- (New York Bantam Books, 2011)
After centuries of bitter strife, the seven powers dividing the land have beaten one another into an uneasy truce. But it's not long before the survivors, outlaws, renegades, and carrion eaters of the Seven Kingdoms gather. Now, as the human crows assemble over a banquet of ashes, daring new plots and dangerous new alliances areformed while surprising faces--some familiar, others only just appearing--emerge from an ominous twilight of past struggles and chaos to take up the challenges of the terrible times ahead. Nobles and commoners, soldiers and sorcerers, assassins and sages, are coming together to stake their fortunes ... and their lives. For at a feast for crows, many are the guests-- but only a few are the survivors.
Keywords: Monarchy -- Fiction; Fantasy; Magic -- Fiction